Eigenvalues of Sturm-Liouville problems with eigenparameter dependent boundary and interface conditions - Zheng, Jiajia; Li, Kun; Zheng, Zhaowen (Mathematical Modelling and Analysis, 2023)
In this paper, a regular discontinuous Sturm-Liouville problem which contains eigenparameter in both boundary and interface conditions is investigated. Firstly, a new operator associated with the problem is constructed, and the self-adjointness of the operator in an appropriate Hilbert space is proved. Some properties of eigenvalues are discussed. Finally, the continuity of eigenvalues and eigenfunctions is investigated, and the differential expressions in the sense of ordinary or Fréchet of the eigenvalues concerning the data are given.